Bioluminescent Antibodies for Point‐of‐Care Diagnostics. (16th May 2017) - Xue, Lin; Yu, Qiuliyang; Griss, Rudolf; Schena, Alberto; Johnsson, Kai
Abstract: We introduce a general method to transform antibodies into ratiometric, bioluminescent sensor proteins for the no‐wash quantification of analytes. Our approach is based on the genetic fusion of antibody fragments to NanoLuc luciferase and SNAP‐tag, the latter being labeled with a synthetic fluorescent competitor of the antigen. Binding of the antigen, here synthetic drugs, by the sensor displaces the tethered fluorescent competitor from the antibody and disrupts bioluminescent resonance energy transfer (BRET) between the luciferase and fluorophore. The semisynthetic sensors display a tunable response range (submicromolar to submillimolar) and large dynamic range (Δ R max >500 %), and they permit the quantification of analytes through spotting of the samples onto paper followed by analysis with a digital camera.